2021
DOI: 10.1002/vms3.610
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the effects of synchronization protocols applied to sheep in Turkey on pregnancy rates during breeding and non‐breeding seasons

Abstract: This study aimed to determine common pregnancy rates and effect sizes with metaanalysis of studies investigating the effect of different synchronization protocols applied to sheep during breeding and non-breeding seasons on pregnancy rates. Common pregnancy rates were estimated by coalescing pregnancy rates of studies performed independently, and heterogeneity between the studies was investigated. The meta-analysis included 24 studies that determined pregnancy rates in 78 different groups consisting of 1934 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The pineal gland secretes the hormone melatonin, and its concentration level rises during the dark period; increased secretion of the hormone melatonin is responsible for inducing ovarian cycles in ewes [65], and continuous administration of the hormone leads to inducing the reproductive season by affecting the hypothalamus gland to secrete the release GnRH hormone and thus the secretion of the hormones LH and FSH from the anterior lobe of the pituitary gland [66]. Treatment of ewes with melatonin improved the reproductive performance of domestic ewes by increasing the fertility rate and the number of additional pregnancies [67].…”
Section: The Use Of the Melatonin Hormonementioning
confidence: 99%
“…The pineal gland secretes the hormone melatonin, and its concentration level rises during the dark period; increased secretion of the hormone melatonin is responsible for inducing ovarian cycles in ewes [65], and continuous administration of the hormone leads to inducing the reproductive season by affecting the hypothalamus gland to secrete the release GnRH hormone and thus the secretion of the hormones LH and FSH from the anterior lobe of the pituitary gland [66]. Treatment of ewes with melatonin improved the reproductive performance of domestic ewes by increasing the fertility rate and the number of additional pregnancies [67].…”
Section: The Use Of the Melatonin Hormonementioning
confidence: 99%
“…Even though meta-analysis is particularly suitable for serial controlled experimental studies, it is used in observational studies as well. Meta-analytical studies also have been conducting in Turkish veterinary obstetrics and gynaecology studies from time to time (4,12).…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…A meta-analysis study conducted in Turkey discovered that pregnancy rates were lower in progesterone + PMSG based estrus synchronization protocols (59.36 %) used in non-breeding season compared to the reproductive period (90.37%). The deep anestrus in animals, diminished hormonal effects, and low ovarian activity are the causes of the low pregnancy rates during the non-breeding season (Arikan et al, 2021). The ovarian follicle population in sheep is known to be highly sensitive to dietary intake, and it has been reported that dietary manipulations can increase both folliculogenesis and ovulation (Scaramuzzi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%